Cutting Words - Polemical Dimensions of Galen's Anatomical Experiments - Salas, Luis Alejandro, (Studies in Ancient Medicine ;, 2021)
In Cutting Words: Polemical Dimensions of Galen's Anatomical Experiments, Luis Alejandro Salas offers a new account of Galen's medical experiments in the context of the high intellectual culture of second century Rome. The book explores how Galen's written experiments operate alongside their live counterparts. It argues that Galen's experimental writing reperforms the licensing functions of his live demonstrations, acting as a surrogate for their performance and in some cases an improvement upon it. Cutting Words focuses on the philosophical targets and theoretical stakes of four case studies: Galen's experiments on voice production, the bladder, the heart, and the femoral artery. Over a millennium later, Vesalius adapted Galen's writing to frame his anatomical studies as a new Galen, securing Galen's legacy of writing.